New records of marine invertebrates from the Cape Verde Islands. - Wirtz, Peter (2008)
The anthozoan Pseudocorynactis caribbeorum den Hartog, 1980, the polychaete Lygdamis wirtzi Nishi and Núñez, 1999, the cirriped Oxynaspis celata Darwin, 1852, the cephalopod Octopus macropus (Risso, 1826), and the phoronid Phoronis australis Haswell, 1883 are recorded from the Cape Verde Islands for the first time.